Stereotactic Radiation for Treating Primary and Metastatic Neoplasms of the Spinal Cord - Liu, Elisa K.; Silverman, Joshua S.; Sulman, Erik P. (Frontiers in Oncology, 2020)
Stereotactic radiation treatment can be used to treat spinal cord neoplasms in patients with either unresectable lesions or residual disease after surgical resection. While treatment guidelines have been suggested for epidural lesions, the utility of stereotactic radiation for intradural and intramedullary malignancies is still debated. Prior reports have suggested that stereotactic radiation approaches can be used for effective tumor control and symptom management. Treatment-related toxicity has been documented in rare subsets of patients, though the incidences of injury are not directly correlated with higher radiation doses. Further studies are needed to assess the factors that influence the risk of radiation-induced myelopathy when treating spinal cord neoplasms with stereotactic radiation, which can include, but may not be limited to, maximum dose, dose-fractionation, irradiated volume, tumor location, histology and treatment history. This review will discuss evidence for current treatment approaches.